PERBANDINGAN MODEL PEMBELAJARAN COOPERATIF LEARNING TIPE JIGSAW DENGAN GROUP RESUME DALAM MENINGKATKAN KEAKTIFAN MAHASISWA - Khairul Anshari (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
The cooperative learning model requires students to be active and discuss, such as the jigsaw and group resume types which both require students to be active in learning. The purpose of this study was to compare the jigsaw type learning method with the group resume in the student development course, in order to see the level of student activity. This study used a comparative descriptive method. The population was all students who took the student development course. The results showed that the activity value in the group resume reached a maximum of 75% and a minimum of 65%, this is because not all students are active in contributing to learning. In the jigsaw type, the maximum activity value was obtained at 76% and a minimum of 68% because students do have a role to be active in every learning process. The student activities observed were viewing activities, listening activities, speaking activities and writing activities with an increase in the values ​​obtained by students. So it can be concluded that the jigsaw model produces more active students.